THE STATE AND PROBLEMS OF THE NATIONAL ECONOMY OF THE UZBEKISTAN SSR (ON THE EXAMPLE OF THE 70-80S OF THE 20TH CENTURY) - Юнусова Х. Э. (TARIXIY TADQIQOTLAR, 2025)
The agriculture of the Uzbek SSR played a significant role not only in the republic's but also in the national economy of the Soviet Union. The Uzbek SSR, in addition to being the country's main cotton base, also produced fresh fruits, grapes, melons and other agricultural products. However, the Soviet state's national economy was plagued by shortages, looting of state property, and annexation. Similar problems existed in other regions of the Uzbek SSR, and are described in this article based on primary sources.